STUDI PERUBAHAN NILAI TANAH DAN PENGGUNAAN LAHAN PADA DAERAH RAWAN GENANGAN BANJIR ROB DI KECAMATAN SEMARANG UTARA - Fanni Kurniawan; Arief Laila Nugraha; Moehammad Awaluddin (Jurnal Geodesi UNDIP, 2013)
North Semarang sub-district has a topography with a slope of 0-2%. The lower area of sea surface will be flooded if the sea surface keep increase with landsubsidence, and also caused by optimallyzation landuse around the coastal area.This research using some secondary data. From the process of merging spotheight with the landsubsidence value every year and then classified by the highest tides, the average of sea level and the lowest tides so obtained the form of tidal inudation area. The fix tidal inudation area model will be overlay with the map of landuse and the land value of North Semarang sub-district. The method used is analysis data based on Geographic Information System with seeing the real condition of the field.The research result shows that the safe area has decrease by 35,5 acres within a period of 7 years. It caused by land use changes such as increase of industry area by 45,3 acres within a period of 5 years. The selling price of land in subcript tidal inudation area such as Tanjung Mas village has increased by Rp. 28.000,00 with AD ground code within a period of 5 years whereas the safe area with AD ground code such as Plombokan village has increased by Rp. 559.000,00 within a period of 5 years.Keywords : tidal inundation, land value, Geographic Information System, landuse